Performance analysis of an integrated scheduling scheme in the presence of bursty MMPP traffic - Liu, Lei; Jin, Xiaolong; Min, Geyong (The Journal of systems and software, 2011)
Contemporary communication networks are expected to support multimedia applications which require diversified Quality-of-Services (QoS). An integrated scheduling discipline of Priority Queueing (PQ) and Generalized Processor Sharing (GPS), referred to as P–G, has recently emerged as a promising scheme for cost-effective QoS differentiation. In this paper, we develop a new analytical model for the integrated P–G system subject to bursty traffic. The Markov-Modulated Poisson Process (MMPP) is adopted to capture traffic burstiness because it can qualitatively model time-varying arrival rate and important correlation between inter-arrival times. To derive the desired performance metrics for individual sessions, the integrated P–G system is decomposed into a set of Single-Server Single-Queue (SSSQ) systems. Specifically, the integrated system is first divided into an SSSQ system and a GPS system. Next, a bounding approach is adopted to decompose the GPS system into individual SSSQ systems. Extensive comparisons between analytical and simulation results validate the accuracy of the analytical model. To demonstrate its merits, the model is used to investigate the configuration of the GPS weights under the QoS constraints of different traffic flows.